Development of Drone for Search and Rescue Operation in Malaysia Flood Disaster - Sobri Hashim, Ahmad; Syafiq Mohamad Tamizi, Mohamad (International Journal of Engineering and Technology, 2018)
2014 drew a very terrible history to Malaysia where this country was hit by the worst flood disaster ever since for the last 20 years. This disaster has caused property lost and few death cases were also reported. Drone, new emergence technology, has the capability to be deployed for search and rescue operation in flood disaster. This technology could improve the operation of search and rescue, reduce the cost incurred and fasten the time to respond when flood happens. It is due to its capability in terms of small scale size of equipment as compared to the conventional search and rescue facilities such as boats, helicopters, etc. Therefore, this paper presents on the development of drone prototype for search and rescue operation in Malaysia flood disaster. The architecture of the software and hardware integration for search and rescue drone has been designed. The experiment was conducted to evaluate on the accuracy of flood victimsâ€™ detection.Â Â